Essential oils of Psidium cattleianum Sabine leaves and flowers: Anti-inflammatory and cytotoxic activities - Elsayed, Heba E.; El-Deeb, Eman M.; Taha, Heba; Taha, Hussein S.; Elgindi, Mohamed R.; Moharram, Fatma A. (Frontiers in Chemistry, 2023)
Introduction:Psidium cattleianum Sabine is a Brazilian native shrub cultivated for its edible fruit araçá (strawberry guava). P. cattleianum is recognized for health and food applications, although the essential oils (EOs) from the Egyptian inhabitant are not fully explored. The current study investigated the anti-inflammatory and cytotoxic activities of EOs from P. cattleianum leaves and flowers. Materials and methods: The EOs were obtained by three different methods viz; the conventional hydro-distillation, microwave assisted hydro-distillation, and supercritical fluid extraction, while their analysis was accomplished using GC/MS. The derived EOs were screened for their anti-inflammatory activity in the 5-lipoxygenase, COX-1, and COX-2 enzyme based assays, while the anticancer potential was deduced from MTT cytotoxic assay, cell cycle, and western blotting analysis. Results and discussion: Among other methods, supercritical fluid extraction offered the highest EO yield, 0.62% (leaves) and 1.4% (flowers). GC/MS identified β-caryophyllene and α-humulene in both organs with high but variable percentages. The leaves demonstrated strong activity in inhibiting the 5-lipoxygenase enzyme (IC50 2.38), while the flowers, in inhibiting COX-2 (IC50 2.575). Moreover, the leaves showed potent, selective cytotoxicity to MCF-7 cells (IC50 5.32) via apoptosis by modulating the p53/Bax/Bcl2 axis. The deduced activities are possible due to the synergism between the volatile components that endorses P. cattleianum leaves’ EOs in the management of breast cancer and inflammatory disorders.